Biofilm Formation in Coagulase-Negative Staphylococci from Various Animals - Bino, Eva; Kandričáková, Anna; Lauková, Andrea (European Journal of Applied Sciences, 2024)
Bacteria show a distinct tendency to "adhere" to various surfaces. This is precisely why many microorganisms occur in the environment in the form of a biofilm and not in a planktonic form. Biofilm formation has been demonstrated in several bacterial species, and hence in staphylococci. Previous studies regarding the staphylococci related to human strains. Antibiotic resistance is currently a problem all over the world, and the formation of biofilm can also affect it, since bacteria that grow in the form of biofilm are much more resistant. The aim of this study was testing biofilm-forming ability in various staphylococci from different animals. One hundred (100) faecal staphylococci from 407 animals were tested. Biofilm formation tested on Congo red agar was confirmed after 72 hours in 81 staphylococci, in 19 strains biofilm was not confirmed on this medium. Using tube method correlation in most cases with the results on Congo red agar was found. Microtiter quantitative plate assay assessed biofilm production in 59 staphylococci out of 100 tested. In a percentage, 96.29% strains from faeces of domestic animals formed biofilm. In the species Staphylococcus vitulinus (14), S. pasteuri (1), S. sciuri (2), S. saprophyticus (1) and S. caprae (1) was biofilm-forming ability detected only using plate assay. To know biofilm-forming ability in huge target of coagulase-negative staphylococci from various animal species is original contribution to biofilm studies.